A phenomenological study of siblings bereaved by suicide: A shared experience. Issue 5 (28th May 2019) - Adams, Elizabeth; Hawgood, Jacinta; Bundock, Anne; Kõlves, Kairi
Abstract: This interpretative phenomenological analysis explored the key issues in the grief experiences of seven young adults bereaved by the youth suicide of a sibling. We conducted semi-structured phone interviews from which we derived four themes describing the participants' experiences of: (a) the process of grief, (b) grief interactions (within families and outside), (c) continuing bonds, and (d) meaning-making and growth through grief. The stories highlight the impact of family relationships on the grieving process in siblings and the need for support to help family members better communicate, understand, and respect each other's needs as they process their grief.